Territorially Embedded Food Systems as a Response to the Challenges of Globalization—Students Understanding, Current Status, Needs, and Expectations of University Education in This Subject Area: A Case from Poland - Klaudia Kopczyńska; Rita Góralska-Walczak; Renata Kazimierczak; Carola Strassner; Alexander Wezel; Paola Migliorini; Dominika Średnicka-Tober (Proceedings)
A concept of resilient, embedded food systems (EFS), environmentally, economically, culturally, socially, and historically linked to certain territories, has been recently gaining attention as a vital response to the globalization of food systems and all its associated challenges. Support for territories on their way to sustain or restore such community-centric, embedded food systems requires transdisciplinary knowledge and skills, and thus effective food system education, including higher education, has an important role to play. The GOODFOOD study looked into the students’ interest in the topic of regional and territorial food systems and their opinion on the importance of certain elements of a food system that is embedded in a region or territory. Students were also asked about the presence of courses or topics related to territorially or regionally embedded food systems in their study programs, their opinion on the usefulness of such courses for their future employment, and the most demanded teaching methods that should be applied to study EFS topics. An online survey carried out among students of the Warsaw University of Life Sciences in Poland of selected study programs related to food science revealed that 70% of respondents are interested in the topic of regional food systems. At the same time, 50% of students have not had any courses related to territorial food systems in their study programs so far, even though over 70% think that such a course would be useful for their future employment. Interactive field trips and excursions, international courses (in a multicultural, international environment), interactive workshops, and cooperation with food system stakeholders (i.e., an internship in a food company) were among the most highly demanded teaching methods to study EFS.